INVENTARISASI JENIS TUMBUHAN PAKAN MONYET HITAM SULAWESI (Macaca nigra) DI TAMAN WISATA ALAM (TWA) BATUPUTIH, SULAWESI UTARA - Pamekas Pamekas; Johny S. Tasirin; Reynold P. Kainde; Maria Y.M.A. Sumakud (Universitas Sam Ratulangi, 2015)
ABSTRACT Â The research was conducted in Batuputih Recreational Park, North Sulawesi with the aim to inventory plant species and feeding frequency of Sulawesi crested-black macaques (Macaca nigra). A group of macaques was followed continuously starting in the morning at the sleeping tree. Observations were made in 15 minute segments including plant species eaten by alfamale, the main female, and another macaques. Plant species and eaten parts were recorded. The results showed that there are 22 species of food plants eaten by the Sulawesi crested- black macaques in Batuputih Recreational Park. The highest eating frquency is kayu sirih (Piper aduncum), Nantu (Palaquium quercifolium), coro (Ficus variegata), aren (Arenga pinata), kelapa (Cocos nucifera), and Seho yaki (Caryota mitis). The macaques ate fruits, shoots and young leaves. Alfamale feed pattern followed almost aligned by the main female and the other macaques except for Cocos nucifera, Dracontomelon dao, Eugenia malaccensis and Morinda bracteata. Exceptions of feeding pattern is that the other macaques have a very high preference in these species in comparison to alfamale and the main female. Feeding range of the macaques were more frequently in shrub land than the secondary forests. Â Keywords: Sulawesi crested-black macaques, Fodder Plant Species, Home Range.